Seismic Analysis and Design of a Multi-Storey Building Located in Haql City, KSA - Mohammed Ismaeil; Khalid Elhadi; Yasser Alashker; Isam Eldin Yousef (Journal of Soft Computing in Civil Engineering, 2017)
Recently the design of RC building to mitigate seismic loads has received great attention. Since Saudi Arabia has low to moderate seismicity, most of the buildings were designed only for gravity load. The objective of this paper is to analysis design RC building located in the most active seismic zone region in Saudi Arabia to mitigate seismic loads. A multi-story reinforced concrete building, in Haql city, was seismically analyzed and designed using the Equivalent Lateral Force Procedure with the aid of SAP200 software. The chosen buildings which were Ordinary Moment Resisting Frame (OMR), was analyzed and designed by using SBC 301 (2007) Saudi Building Code [1], SAP2000 (structural analysis software) [2] and ISACOL "Information Systems Application on Reinforced Concrete Columns" [3]. The results showed that the current design of RC buildings located in the most active seismic zone region in Saudi Arabia, Haql city was found unsafe, inadequate and unsatisfied to mitigate seismic loads.